2022
DOI: 10.3390/molecules27196759
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus ochraceus: Metabolites, Bioactivities, Biosynthesis, and Biotechnological Potential

Abstract: Fungus continues to attract great attention as a promising pool of biometabolites. Aspergillus ochraceus Wilh (Aspergillaceae) has established its capacity to biosynthesize a myriad of metabolites belonging to different chemical classes, such as isocoumarins, pyrazines, sterols, indole alkaloids, diketopiperazines, polyketides, peptides, quinones, polyketides, and sesquiterpenoids, revealing various bioactivities that are antimicrobial, cytotoxic, antiviral, anti-inflammatory, insecticidal, and neuroprotective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 105 publications
1
9
0
Order By: Relevance
“…These enzymes have important biotechnological applications in the food and beverages, textile, detergent, paper and pulp, pharmaceutical and medical industries [ 61 ]. Aspergillus ochraceus produces a variety of enzymes which have biotechnological and industrial values as reported by Hareeri et al [ 62 ]. Isolate F25 was no different and produced the seven enzymes included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes have important biotechnological applications in the food and beverages, textile, detergent, paper and pulp, pharmaceutical and medical industries [ 61 ]. Aspergillus ochraceus produces a variety of enzymes which have biotechnological and industrial values as reported by Hareeri et al [ 62 ]. Isolate F25 was no different and produced the seven enzymes included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A. ochraceus is widely distributed in soils and various agricultural commodities and is also known as a food pathogen [ 30 ]. However, this fungus can synthesize diverse beneficial metabolites, including polyketides, alkaloids, steroids, peptides, and quinones, with promising bioactivities [ 31 ]. For example, three asperochrins with significant antibacterial activity against aquatic pathogenic bacteria were obtained from the marine mangrove-derived fungus A. ochraceus [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of its species also have potential applications in biotechnology and industry. [4][5][6][7][8] Notably, A. nidulans is recognized for its rich reservoir of bioactive metabolites, which exhibit a wide array of biological properties such as antioxidants, antibacterial, antiviral, plant growth promotion, cytotoxicity, anti-inflammatory, and antimicrobial. [8,9] In our program to discover antimicrobial agents from marinederived fungi, the ethyl acetate extract (EtOAc) of sponge derived-fungus Aspergillus nidulans M256 exhibited antimicrobial activity (MICs: 128-256 μg/mL) against five-microorganism strains including Gram-positive bacteria (Enterococcus faecalis, Staphylococcus aureus, Bacillus cereus), Gram-negative bacteria (Salmonella enterica), and yeast (Candida albicans).…”
Section: Introductionmentioning
confidence: 99%
“…Among these, the Aspergillus genus stands out as a prolific producer of diverse metabolites with numerous biological activities. Some of its species also have potential applications in biotechnology and industry [4–8] . Notably, A. nidulans is recognized for its rich reservoir of bioactive metabolites, which exhibit a wide array of biological properties such as antioxidants, antibacterial, antiviral, plant growth promotion, cytotoxicity, anti‐inflammatory, and antimicrobial [8,9] .…”
Section: Introductionmentioning
confidence: 99%